Peritoneal HPV‐DNA test in cervical cancer (PIONEER study): A proof of concept. Issue 5 (27th November 2020) - Bizzarri, Nicolò; Pedone Anchora, Luigi; Cattani, Paola; De Vincenzo, Rosa; Marchetti, Simona; Conte, Carmine; Chiantera, Vito; Gallotta, Valerio; Gueli Alletti, Salvatore; Vizzielli, Giuseppe; Costantini, Barbara; Fagotti, Anna; et al.
Abstract: The aim of this study was to investigate the prevalence of peritoneal human papillomavirus (HPV) infection in different clinical cervical cancer (CC) settings, and its association with potential clinical and/or histological factors. This is a single‐center, prospective, observational study. Consecutive patients with newly diagnosed or recurrent/persistent CC, between March 2019 and April 2020, were included. A group of patients undergoing surgery for benign gynecological conditions was included as control group. All patients underwent HPV‐DNA test in the cervix and in the peritoneal cavity simultaneously at time of surgery. Two‐hundred seventy‐two patients had cervical and peritoneal HPV test analyzed. Cervical and peritoneal HPV positivity (PHP) was found in 235 (88.0%) and 78 (28.7%) patients, respectively; the prevalence of PHP was 17.7% in early stage, 28.8% in locally advanced cervical cancer (LACC) and 46.6% in the metastatic/persistent/recurrent setting ( P = .001). No control patient was found to have peritoneal HPV infection. Higher frequency of PHP was documented in patients with larger tumor size ( P = .003), presence of cervical HPV 16/18 genotypes ( P < .001), higher number of cervical high‐risk (HR)‐HPV per patient ( P = .018) and peritoneal carcinomatosis ( P < .001). Multivariate analysis demonstrated that lack of preoperative cervical conization in early stages ( P = .030), while higher International Federation of Gynecology and Obstetrics (FIGO) stage ( P = .021) and presence of cervical HPV 16/18 ( P = .001) in LACC, was associated with PHP. This is a proof‐of‐concept study. A number of potential clinical implications, including prognosis, could be obtained by further studies. Abstract : What's new? The spread of cervical cancer to the peritoneum is not well understood. In particular, the extent to which human papillomavirus (HPV) colonization of the peritoneum is associated with peritoneal carcinomatosis remains unknown. In the present investigation of peritoneal HPV infection in different clinical settings of cervical cancer, peritoneal HPV positivity was correlated with other known prognostic markers, including large tumor size and more advanced disease. The findings suggest that the presence of HPV in the peritoneal cavity is a clinical marker of locally advanced cervical cancer and may indicate predisposition to HPV infection persistence, a determinant of disease progression.